2021
DOI: 10.3390/ijerph18189936
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Tolerant Compatible Microbial Inoculants Modulate Physio-Biochemical Responses Enhance Plant Growth, Zn Biofortification and Yield of Wheat Grown in Saline-Sodic Soil

Abstract: A wide range of root-associated mutualistic microorganisms have been successfully applied and documented in the past for growth promotion, biofertilization, biofortification and biotic and abiotic stress amelioration in major crops. These microorganisms include nitrogen fixers, nutrient mobilizers, bio-remediators and bio-control agents. The present study aimed to demonstrate the impact of salt-tolerant compatible microbial inoculants on plant growth; Zn biofortification and yield of wheat (Triticum aestivum L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 100 publications
1
28
0
Order By: Relevance
“…All these findings recommend the salinity mitigation role of α-tocopherol as a shielding agent by protecting chlorophyll pigments from photoinhibition. Agricultural crops suffer severe nutritional disorders due to competition among Na + , Ca 2+ , and K + ions ( Singh et al, 2021 ). In this study, higher concentrations of Na + were observed in the leaf and root tissues of okra plants under saline regimes.…”
Section: Discussionmentioning
confidence: 99%
“…All these findings recommend the salinity mitigation role of α-tocopherol as a shielding agent by protecting chlorophyll pigments from photoinhibition. Agricultural crops suffer severe nutritional disorders due to competition among Na + , Ca 2+ , and K + ions ( Singh et al, 2021 ). In this study, higher concentrations of Na + were observed in the leaf and root tissues of okra plants under saline regimes.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression analysis, which has been proven from recent studies, clearly showed that Zn-solubilizing microbial inoculants and other plant growth-stimulating microbes modulate the expression patterns of some of the genes from the Zn-regulated transporter family and thus played an important role in the transmission of Zn in the different parts of plants (143,159). The co-inoculation of Trichoderma harzianum (UBSTH-501) and Bacillus amyloliquefaciens (B-16) augmented the expression level of the ZIP transporters genes ("TaZIP-1, " "TaZIP-3, " "TaZIP-5, " "TaZIP-6, " "TaZIP-7, " "TaZIP-10, " and "TaZIP-13") by 2.76-4.96-folds, which eventually led to increased Zn translocation in wheat cultivated in saline-sodic soil (159). Besides ZSB, mycorrhizal fungi also showed their contribution in biofortification (160).…”
Section: Current Insights On Molecular Aspects Of Microbial-assisted Zn Biofortificationmentioning
confidence: 99%
“…In recent research, gene expression analysis was used to demonstrate that Znsolubilizing microbial biostimulants, along with other plant growth-stimulating microbes, influence the expression profiles of some of the Zn-regulated transporter family genes and, as a result, play a key role in the transport of zinc to the various plant parts (Krithika and Balachandar, 2016;Upadhayay et al, 2022a). The co-inoculation of Trichoderma harzianum and Bacillus amyloliquefaciens led to a 2.76-4.96-fold increase in the expression of the ZIP transporter gene in wheat, which resulted in enhanced zinc transport (Singh et al, 2021). In addition to addressing zinc deficiency, Zn-solubilizing microorganisms can also be used to enhance the productivity of food crops.…”
Section: Bacterial Role In Zinc Biofortificationmentioning
confidence: 99%